A Retrospective Chart Review to Examine Intra-Compartment Pressures and Post-Operative Outcomes of Chronic Exertional Compartment Syndrome. Issue 4 (22nd October 2020) - Brower, Jacob; Shuster, David M.; Cheney, Nicholas A.; Clark, Brian C.
Category: Other Introduction/Purpose: Chronic exertional compartment syndrome (CECS) is defined as reversible, insufficient blood supply to a fascial compartment's contents. Patients with this condition have abnormally elevated pressures within specific fascial compartments, causing decreased blood flow to that area. This temporary loss of blood supply produces a feeling of tightness in the affected muscles, pain, and possibly local paresthesia. Surgical treatment involves a fasciotomy, which releases the implicated compartment's fascia. This procedure creates additional space for muscle expansion and more adequate blood supply to the appropriate tissues.The purpose of this study is to review the surgical outcomes of patients diagnosed with lower extremity CECS whom received a fasciotomy, assessing correlations between resting intramuscular compartment pressures and surgical outcomes. Methods: A retrospective chart analysis was performed of the senior author's patients between January 1st, 2013 and June 30th, 2019. Patients included in this study presented with symptoms consistent with lower extremity CECS and had the diagnosis confirmed, either unilaterally or bilaterally, via the resting intramuscular pressure cutoff (>=15 mmHg) outlined by the Pedowitz criteria. These patients subsequently received fasciotomies for the syndrome. Results: Out of the 37 patients included in this study, 30 (81.1%) reported improvement in their post-operative pain scores. There was a trend (P > 0.1523) between resting intra-compartment pressures and post-operative pain improvement. Conclusion: Our study suggests a positive trend between higher resting intra-compartment pressures and post-operative pain improvement. Due to the limited number of study participants, no correlations could be determined. However, this data is significant because it demonstrates the importance of the Pedowitz diagnostic criteria, as it is the first study showing a relationship between the resting pressure criteria and surgical outcomes. Further research is necessary to determine if there is a correlation between higher intramuscular pressures and positive surgical outcomes.